Self-Prioritization Effect in Children and Adults - Singh, Divita; Karnick, Harish (Frontiers in Psychology, 2022)
Self-related information is processed with priority, an effect known as the self-prioritization effect (SPE). Recent studies on SPE show enhanced cognitive processing of the newly learned self-association compared to non-self (such as mother, friend, and stranger) associations among younger and older adults. However, developmental influences on the magnitude of SPE remains poorly understood. In order to examine the developmental impacts on the SPE, in the present study, we recruited participants ranging from 9-22 years of age and divided them into three age groups: older children (age 9-13), teenagers (age 14-17), and young adult (age 18-22) and compared their performance in the matching judgement task. Our results show more significant bias towards self than mother, friend, or stranger condition in all the three age groups, showing robust SPE in the 9-22-year-old age group. We also observed a more significant bias towards mother-association than friend and stranger-association in all the age groups showing an enhanced bias towards mother. Our study extends the SPE in older children and teenagers and shows that SPE remains robust and stable throughout childhood.